Gestaltungsprinzipien spätantiker Grabräume Untersuchungen zu visuellen Strukturen und Wirkungsmechanismen in der römischen Katakombenmalerei - Fugger, Verena (Verlag der Österreichischen Akademie der Wissenschaften, 2023)
The book deals with the pictorial design principles of late antique burial chambers, such as those created in the Roman catacombs between the 3rd and 4th centuries A.D. in the form of private cubicula. With the help of an approach oriented towards visual studies and reception aesthetic that focuses on the interrelationship between space, image and viewer, the study systematically analyzes for the first time regularities in the disposition and combination of Christian motifs. However, the shown design principles occurring in the Roman catacombs are not locally restricted to Rome, but rather should be understood as basic phenomena of the late antique visual culture, as the study demonstrates by a comparative perspective on the Roman provinces.